The Effect of Feeding Starter Diets for Different Periods on Performance of Broilers - Baha Eddin Abu-Bakr (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
A total of 150 birds were used in this experiment in summer 2002 to investigate the effect of feeding starter diets for different periods on the performance and the economical advantages on broiler chicks. Birds were fed starter diets for two, three and four weeks prior to feeding the finisher diets. Birds fed the starter for four weeks had higher (p